2015
DOI: 10.1186/s12985-015-0298-0
|View full text |Cite
|
Sign up to set email alerts
|

HIV infection and antiretroviral therapy lead to unfolded protein response activation

Abstract: BackgroundThe unfolded protein response (UPR) is one of the pathways triggered to ensure quality control of the proteins assembled in the endoplasmic reticulum (ER) when cell homeostasis is compromised. This mechanism is primarily composed of three transmembrane proteins serving as stress sensors: PKR-like ER kinase (PERK), activating transcription factor 6 (ATF6), and inositol-requiring enzyme 1 (IRE1). These three proteins’ synergic action elicits translation and transcriptional downstream pathways, leading … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 42 publications
3
30
1
1
Order By: Relevance
“…Another key ER stress sensor is IRE1, an endonuclease that cleaves a sequence of XBP1 mRNA and its processing into a newly spliced protein that functions as a transcription factor for genes involved in the ER‐resident protein folding and degradation reactions . Similarly to others UPR markers assayed, our findings demonstrate that Tat stimuli also significantly induces expression of the IRE1‐XBP1 axis, in line with the literature . Interestingly, it has been reported that a viral‐induced IRE1 branch activation is involved in both ER homeostatic restoration and cellular survival, and in the triggering of several apoptosis‐regulating mechanisms .…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Another key ER stress sensor is IRE1, an endonuclease that cleaves a sequence of XBP1 mRNA and its processing into a newly spliced protein that functions as a transcription factor for genes involved in the ER‐resident protein folding and degradation reactions . Similarly to others UPR markers assayed, our findings demonstrate that Tat stimuli also significantly induces expression of the IRE1‐XBP1 axis, in line with the literature . Interestingly, it has been reported that a viral‐induced IRE1 branch activation is involved in both ER homeostatic restoration and cellular survival, and in the triggering of several apoptosis‐regulating mechanisms .…”
Section: Discussionsupporting
confidence: 89%
“…Many mammalian viruses have evolved to manipulate UPR signalling pathways in host cells to promote viral translation and persistence in infected cells. With specific reference to HIV, it has been shown that UPR‐related proteins are up‐regulated in HIV target cells in vitro or in cells derived from HIV‐infected patients, demonstrating that viral UPR modulation enhances HIV replication and contributes to successful infection . To assess the potential coupling of apoptotic fate and ER stress responses induced by circulant Tat, we performed real‐time mRNA quantification by PCR method to assess the expression levels of crucial ER stress/UPR signature markers and their central downstream effectors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Viral infection will influence cell response and may activate HSF1 and its downstream HSPs (21). Therefore, the J-lat 10.6 cell line, which does not produce viruses, was employed in our following research.…”
Section: Pis Reactivate Latent Hiv In Both Latency Cell Models and Prmentioning
confidence: 99%
“…Epidemiological studies demonstrated that while endothelial dysfunction is reduced following HAART initiation, long term exposure to ARVd leads to the development of vasculopathy, especially with the usage of certain protease inhibitors3435. These conditions could arise from chronic induction of ER stress3637, an increase in local inflammation38, or apoptosis activation39.…”
mentioning
confidence: 99%